Association between dietary quality and executive functions in school-aged children with autism spectrum disorder - Wang, Xin; Song, Xiaojing; Jin, Yuying; Zhan, Xiaoling; Cao, Muqing; Guo, Xuning; Liu, Siyu; Ou, Xiaoxuan; Gu, Tingfeng; Jing, Jin; Cai, Li; Li, Xiuhong (Frontiers in Nutrition, 2022)
Background: It is well known that children with autism spectrum disorder (ASD) had executive functions deficit. However, it is still unclear whether the poor dietary quality is related to the impairment of executive functions. The current study aimed to explore the association between dietary quality and executive functions in children with ASD. Methods: A total of 106 children with ASD (7.7±1.3 years) and 207 typically developing (TD) children (7.8±1.3 years) were enrolled from Guangzhou, China. The Chinese version of Behavior Rating Scale of Executive function (BRIEF), the working memory subscales of the Chinese version of Wechsler Intelligence Scale for Children-Fourth Edition (WISC-Ⅳ), and the Stroop Color-Word Test (SCWT) were used to measure the participant’s executive functions. The food frequency questionnaire (FFQ) was used to collect the dietary intake information, and the Chinese Diet Balance Index (DBI_16) was used to evaluate the dietary quality. Generalized linear models were used to estimate the association between dietary quality and executive functions. Results: In children with ASD, Low Bound Score (LBS) was positively correlated with the working memory subscale score of BRIEF (β=0.23, 95%CI: 0.02-0.44, P<0.05), while High Bound Score (HBS) and LBS were positively correlated with the organizable subscale score of BRIEF (β=0.44, 95%CI: 0.11-0.77, P<0.01; β=0.19, 95% CI: 0.01-0.37, P<0.05). Compared to TD children, children with ASD had a higher proportion of moderate and high levels of insufficient dietary intake (moderate level, 37.7% vs. 23.2%, high level, 4.7% vs. 1.4%) and moderate level of unbalanced dietary intake (36.8% vs.21.3%), higher scores on all subscales of BRIEF (P<0.01), and lower score on the working memory (81.3±32.3 vs. 104.6±12.5, P<0.01), while there was no difference on the SCWT. Conclusion: Poor dietary quality was associated with the impairment of working memory and organizational capacity in children with ASD. This study emphasized the importance of dietary quality in executive functions among children with ASD, and attention should be paid to improving their dietary quality.